Effect of linear chain carboxylic acid anhydrides on physical and mechanical properties of rubber (Hevea brasiliensis), acacia, (Acacia spp.), and oil palm (Tinnera spp.) woods - Mohtar, Mohd Afiq; Hamid, Norul Hisham; Sahri, Mohd Hamami (Hindawi Publishing Corporation, 2014)
The physical and mechanical properties of Rubber wood, Acacia wood, and Oil palm wood that reacted with acetic, propionic, and butyric anhydrides using a microwave heating for 4 minutes were investigated. A sample dimension of 300 mm × 100 mm × 25 mm (L x W x T) was used for modification and they were cut into smaller specimens for different testing method. This study found that the density increment and void volume changes were not significantly different from anhydrides. The modification of wood with anhydrides was not significantly affected by the static bending properties, except for the Oil palm. The compression strength for any anhydrides shows an improvement for the Rubber wood and Acacia spp. but not Oil palm. The hardness was also not significantly different from anhydrides for all wood species. The impact strength of Rubber wood and Oil palm significantly increased compared to the untreated wood, but this was not the case for Acacia spp. Generally, the highest improvement in mechanical properties was obtained by modification of Rubber and Acacia woods with butyric anhydride.